Tree Structure Based Algorithm for Multiobjective Optimization of Switch Allocation in Radial Distribution Networks - Galias, Zbigniew (2019 IEEE PES GTD Grand International Conference and Exposition Asia (GTD Asia), 2019)
Reducing the consequences of outages in power distribution networks can be achieved by the installation of sectionalizing switches, which may be activated to isolate faulty elements. Positions of sectionalizing switches are usually selected to minimize a given reliability factor. In general, optimization of one of the reliability factors is not equivalent to the minimization of other factors. An optimization algorithm to solve the problem of the optimal switch placement to simultaneously minimize several reliability factors is presented. The algorithm is designed for single-feeder distribution networks with a radial topology. The performance of the algorithm is assessed using an existing distribution network of a moderate size.